"In our community, we normalize pain": discussions around menstruation and uterine fibroids with Black women and Latinas - Minerva Orellana; Karen. N DSouza; Jane Q. Yap; Abhirami Sriganeshan; M. Elena Jones; Charis Johnson; Megan Allyse; Sateria Venable; Elizabeth A. Stewart; Felicity Enders; Joyce E. Balls-Berry (BMC, 2024)
Abstract Background Uterine fibroids are non-cancerous neoplasms that arise from the uterus affecting over 75% of women. However, there is a disparity with Black women having an increased prevalence of nearly 80%. Black women also experience increased symptom burden, including younger age at the time of diagnosis and increased number and volume of fibroids. Less is known about other ethnoracially diverse women such as Latinas and the potential cultural impacts on fibroid burden and treatment. Methods Community engagement studios were conducted to facilitate discussions with stakeholders on their uterine fibroid and menstruation experience. We recruited Black women (n = 6) diagnosed with uterine fibroids and Latinas (n = 7) without uterine fibroids. We held two virtual community engagement studios split by uterine fibroid diagnosis. The studios were not audio recorded and notes were taken by four notetakers. The notes were thematically analyzed in Atlas.ti using content analysis. Results Participants felt there was a lack of discussion around menstruation overall, whether in the home or school settings. This lack of menstruation education was pronounced when participants had their first menstruation experience, with many unaware of what to expect. This silence around menstruation led to a normalization of painful menstruation symptoms. When it came to different treatment options for uterine fibroids, some women wanted to explore alternative treatments but were dismissed by their healthcare providers. Many participants advocated for having discussions with their healthcare provider about life goals to discuss different treatment options for their uterine fibroids. Conclusion Despite uterine fibroid diagnosis, there is silence around menstruation. Menstruation is a normal biological occurrence and needs to be discussed to help prevent delayed diagnosis of uterine fibroids and possibly other gynecological disorders. Along with increased discussions around menstruation, further discussion is needed between healthcare providers and uterine fibroid patients to explore appropriate treatment options.